Plan estratégico para la microempresa “Más Café Palanda” del cantón Palanda, provincia de Zamora Chinchipe. - Vargas Macao, Jimmy Rodrigo (2024)
Every strategic plan is a tool that allows a company to capture all the decisions to be applied in the short, medium and long term, establishing strategies to achieve them. The objective of this research is “to develop a strategic plan for the microenterprise “MÁS CAFÉ PALANDA”, in order to improve internal activities and overcome deficiencies in the company”; applying a diagnosis, and using the descriptive method and different research techniques, which made it possible to collect necessary information and establish the real situation of the company. Carrying out an external analysis (PEST), considering Porter's five forces and thus establishing the opportunities and threats that the company presents; The internal analysis was based on the different activities carried out in the organization, both in the administrative part, human resources, marketing, production and accounting, thus establishing its strengths and weaknesses, (MEFI); Then we proceeded to prepare the SWOT and establish the policies and strategies to be applied by the company, to improve its performance, to finally prepare a proposal to improve its situation. Concluding that the company “Más café Palanda” requires incorporating a strategic plan that allows it to expand its markets, attract new customers, improve its production and commercial process, among the results it can be identified that the time that the process will last is three years, distributed into 5 objectives, with their respective strategy, the total investment is USD 6,900.00, distributed USD 3,100, year 1; USD 1,900 year 2 and 3 respectively, considering training, marketing, strategic alliances, etc.